Performance of Shallots (Allium Ascalonicum L) in Peat Soil with Organic Fertilizer and Arbuscular Mycorrhizal Fungi (AMF) - Riki Warman; Putri Tria Santari; Nofrita Sandi (Jurnal Penelitian Pendidikan IPA, 2022)
Peat soil has the potential and is widely available to be used for shallot cultivation with good and proper management, peat land is classified as marginal land for various types of plants because the soil condition is saturated with water, reacts acidic and contains toxic organic acids and low nutrient status so the condition of plant root media that is not conducive to root development so that it becomes a limiting factor in shallot cultivation. Efforts to increase peatland productivity for shallot cultivation can be carried out by adding organic fertilizers and using rhizosphere microorganisms such as Abuscular Mycorrhizal Â Fungi (AMF), this study aims to get a dose of organic fertilizer and AMF which can increase shallot production on peat soil. The research method used a separate experimental design (Split Plot) Completely Randomized DesignÂ  which consisted of 2 factors, namely: AMF treatment (M) main plot consisting of 2 levels (without AMF application and AMF application), the second factor was the dose of organic fertilizer (O) child plot consisting of 6 levels (0 tons ha-1 , 3 tons ha-1, 6 tons ha-1, 9 tons ha-1, 12 tons ha-1 and 15 tons ha-1) there were 12 treatments each repeated 3 times, which was carried out in January-April 2021 in Pontianak City with the parameters of observing plant height, number of leaves, number of tillers, harvested dry tuber weight, harvested dry plant weight and tuber diameter. and the number of leaves, while the AMF treatment independently had a significant effect on the observation of the number of tillers, the weight of harvested dry tubers, the weight of harvested dry plants and the treatment of organic fertilizer with a dose of 3 tons h-1 showed good results because they were not significantly different from the required mines 15, 12 and 6 tons ha-1 .